1990
DOI: 10.2337/diacare.13.7.796
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Reported Family History of Diabetes Mellitus: Results From San Luis Valley Diabetes Study

Abstract: There are two possible sources of bias in the assessment of family history of diabetes: 1) a person with diabetes may be more likely to report a diabetic relative than a nondiabetic person would be, and 2) relatives of individuals with diabetes may be more likely to be tested for diabetes than relatives of nondiabetic individuals. We conducted a study on a subsample of families of subjects in the San Luis Valley Diabetes Study to examine these issues. A sample of 5 White and 5 Hispanic subjects (probands) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 1 publication
1
35
2
1
Order By: Relevance
“…Thorand et al (36) stated that this could explain the higher prevalence of maternal history of DM. However, Kahn et al (37) concluded that patients with DM were able to report an accurate family history when carefully questioned. Another possible source of bias is the fact that the life expectancy of men is shorter than that of women, and thus the likelihood of DM diagnosis is higher in women.…”
Section: Discussionmentioning
confidence: 99%
“…Thorand et al (36) stated that this could explain the higher prevalence of maternal history of DM. However, Kahn et al (37) concluded that patients with DM were able to report an accurate family history when carefully questioned. Another possible source of bias is the fact that the life expectancy of men is shorter than that of women, and thus the likelihood of DM diagnosis is higher in women.…”
Section: Discussionmentioning
confidence: 99%
“…Thorand et al (26), investigating the association between DM and parental history among the participants of the MONICA Augsburg Study, reported that "unknown" maternal status was more common than "unknown" paternal status (17.3% versus 8.8%), concluding that the higher prevalence of maternal history could be explained by this bias. However, Kahn et al (27) concluded that patients with DM were able to report an accurate family history when carefully questioned. The present data suggests that this bias had not occurred because the patients answered that did not know the familial history of type 2 DM in a similar frequency to the maternal and paternal line of the family.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a validation study of family history of diabetes, there was complete agreement between information about diabetic status reported by patients in a clinic and the information given by respective relatives in a follow-up interview. 21 Disease that occurs at earlier ages and results in more severe morbidity will likely be reported more accurately than disease that occurs late in life and is less severe. Diseases for which there may be some stigma, such as schizophrenia or alcoholism, may be reported less reliably.…”
Section: Analytic Validitymentioning
confidence: 99%